Urban Agrarian Reform as a Legal Effort by Communities to Defend Their Land Tenure Rights - Irene Mariane (Faculty of Law, Universitas Pekalongan, 2022)
Urban agrarian reform is a significant issue in Indonesia, often overshadowed by rural land disputes. Rapid urbanization in major cities such as Jakarta, Surabaya, and Bandung has led to complex land conflicts, particularly affecting people living in informal settlements with unclear land ownership status. This study aims to explore the legal measures available to urban communities to defend their land rights amidst forced evictions and inadequate relocation solutions. Using a literature review approach, data was collected from academic journals, books, policy reports, and official government documents. The analysis identified key themes such as unclear land ownership status, inadequate compensation, and relocation, as well as the legal barriers faced by affected communities. The findings highlight the need for transparent mediation processes, fair compensation, and effective land titling programs to ensure social justice and sustainable urban development. By strengthening civil society organizations and fostering collaboration between government, communities, and NGOs, the study proposes strategies to improve the effectiveness of urban agrarian reform in Indonesia